Ascites as a Predictive Factor in Malignancies in the Last Year of Life-Comparison Between Different Cancer Types - Fridegren, Johan; Björkhem-Bergman, Linda; Schultz, Torbjörn; Strang, Peter (Journal of palliative medicine, 2025)
Ascites in malignancies is usually associated with poor prognosis, but the predictive value may vary between different cancer types. The aim was to map the frequency and temporal pattern of paracentesis in patients with malignancies in relation to time to death and to evaluate the occurrence of ascites as a predictive factor in different cancer types, with a limitation to the last year of life. A retrospective study based on registry data covering all care visits in the Stockholm Region, Sweden, for seven years was performed. All deceased subjects that had at least one registered paracentesis in the last year of life were included. Of 23,056 subjects dying from cancer, 1863 had undergone paracentesis in the last year of life (8.0%). Ascites requiring paracentesis was most frequently seen in appendiceal cancer (38%), ovarian cancer (35%), cholangiocarcinoma (26%), hepatocellular carcinoma (19%), and pancreatic cancer (17%). The median time for the first paracentesis in all cancer types varied between 248 and 20 days before death. For ovarian cancer, the median time for first paracentesis differed significantly compared with upper gastro-intestinal (GI) cancers, 81 days compared with 30 days ( < 0.0001). Ascites in prostate cancer was rare,1.9%, but when present, a pronounced increase in the frequency of paracentesis was observed in the last three months of life. The occurrence of paracentesis in patients with advanced cancer is generally a sign that death is approaching within the coming months, especially in upper GI cancer. For ovarian and appendiceal cancers, ascites is less useful as a predictive tool.